Galician Monks and Monasteries in Portugal (12th – 15th Centuries) - Pérez Rodríguez, Francisco Javier (2022)
This paper identifies the Galician monasteries with real estate in the Kingdom of Portugal between the 12th and 15th centuries and analyses and characterizes such property. The policy of Portuguese monarchs regarding such property is also analysed while paying particular attention to political relations between Portuguese and Spanish kings. The ecclesiastical relations between Galician monasteries and the neighbouring kingdom are also subject of study: basically, the existing data at the archbishop's see of Braga –metropolitan see up to the Western Schism – and the pontifical authorization granted to Galician abbots to intervene in Portuguese affairs. Finally, a brief reference is made to the cultural and spiritual role of Galician monasteries in the neighbouring kingdom.   Bibliography Handwritten sources Tui, Arquivo da Catedral, Becerro 1, fols. 44r-52v e fols. 111v-114r. Tui, Arquivo da Catedral, Pergameos, Carpeta 10, doc. 16. Tui, Arquivo da Catedral, Pergameos, Carpeta 12, doc. 14.  Printed sources  ANDRADE CERNADAS, José Miguel – O Tombo de Celanova. Santiago de Compostela: Consello da Cultura Galega, 1995. AZEVEDO, Rui Pinto de (ed.) – Documentos medievais portugueses. Documentos régios. Vol. I: Documentos dos condes portugalenses e de D. Afonso Henriques, A.D. 1095-1185. Lisboa: Academia Portuguesa da História, 1958. BLANCO LOZANO, Pilar – Colección diplomática de Fernando I (1037-1065). León: Centro de Estudios e Investigación San Isidoro – Archivo Histórico Diocesano, 1987. COSTA, Avelino de Jesus da (ed.) – Liber Fidei Sanctae Bracarensis Ecclesiae. Tomo I. Braga: Assembleia Distrital, 1978. COSTA, Avelino de Jesus da (ed.) – Liber Fidei Sanctae Bracarensis Ecclesiae. Tomo II. Braga: Junta Distrital, 1965. COSTA, Avelino de Jesus da; MARQUES, Maria Alegria F. – Bulário Português. Inocencio III (965-1216). Coimbra: Instituto Nacional de Investigação Científica, 1989. LA CUEVA, Benito de – Historia de los monasterios y prioratos anejos a Celanova. Edición, notas e índices por María Teresa González Balasch. Granada: Universidad de Granada, 1991. LORENZO, Ramón – Colección documental do mosteiro de Montederramo. Santiago de Compostela: Consello da Cultura Galega, 2016, 3 tomos. LUCAS ÁLVAREZ, Manuel – El Tumbo de San Julián de Samos (siglos VIII-XII). Estudio introductorio. Edición diplomática. Apéndices e índices. Santiago de Compostela: Caixa Galicia, 1986. LUCAS ÁLVAREZ, Manuel – San Paio de Antealtares, Soandres y Toques: tres monasterios medievales gallegos. Sada: Seminario de Estudios Galegos–Ediciós do Castro, 2001. LUCAS ÁLVAREZ, Manuel; LUCAS DOMÍNGUEZ, Pedro Pablo – San Pedro de Ramirás. Un monasterio femenino en la Edad Media. Colección diplomática. Santiago de Compostela: Caixa Galicia, 1988. MANSILLA REOYO, Demetrio – La documentación pontificia de Honorio III (1216-1227). Roma: Instituto Español de Estudios Eclesiásticos, 1965. PICHEL GOTÉRREZ, Ricardo – Fundación e primeiros séculos do mosteiro bieito de Santo Estevo de Chouzán (sécs. IX-XIII). Noia: Toxosoutos, 2009. PIZARRO, José Augusto de Sottomayor – Inquisitiones. Inquirições gerais de D. Dinis de 1288, sentenças de 1290 e execuções de 1291. Lisboa: Academia das Ciências de Lisboa, 2012. Portugaliae Monumenta Historica a saeculo octavo post Christum usque ad quintundecimum. Inquisitiones. Volumen I, fasciculus III. Lisboa: Academia das Ciências de Lisboa, 1891. Portugaliae Monumenta Historica a saeculo octavo post Christum usque ad quintundecimum. Inquisitiones. Volumen I, fasciculi IV et V. Lisboa: Academia das Ciências de Lisboa, 1897. Portugaliae Monumenta Historica a saeculo octavo post Christum usque ad quintundecimum. Inquisitiones. Volumen I, fasciculus VIII. Lisboa: Academia das Ciências de Lisboa, 1961. RODRÍGUEZ R. DE LAMA, Ildefonso – La documentación pontificia de Urbano IV (1261-1264). Roma: Instituto Español de Historia Eclesiástica, 1981. ROMANÍ MARTÍNEZ, Miguel – Colección diplomática do mosteiro cisterciense de Santa Maria de Oseira (Ourense), 1025-1310. Santiago de Compostela: Departamento de Historia I, 1989. SÁNCHEZ BELDA, Luis – Documentos reales de la Edad Media referentes a Galicia. Madrid: Dirección General de Archivos y Bibliotecas, 1953. VAQUERO DÍAZ, María Beatriz – Colección diplomática do mosteiro de San Salvador de Celanova (ss. XIII-XV). Ourense: Concello de Celanova / Universidade de Vigo, 2004. ZARAGOZA I PASCUAL, Ernest – “Proceso de reforma contra la abadesa de San Salvador de Albeos (1499)”. Museo de Pontevedra, 51 (1997), pp. 563-590.  Studies ANDRADE CERNADAS, José Miguel – El monacato benedictino y la sociedad de la Galicia medieval (siglos X al XIII). Sada: Seminario de Estudios Galegos / Ediciós do Castro, 1997. BECEIRO PITA, Isabel – “Las tensiones en torno a los dominios del Cister gallego en el norte de Portugal”. In Actas. Congreso Internacional sobre san Bernardo e o Císter en España e Portugal. Ourense: Monasterio de Oseira, 1992, t. 1, pp. 253-265. DURO PEÑA, Emilio – “El monasterio de Santa Marina de Asadur”. Archivos Leoneses 27 (1973), pp. 309-365. FERNANDES, A. de Almeida, “Portugal no período vimaranense (868-1128)”. Revista de Guimarães 81 (1971), pp. 51-98. GONZÁLEZ, Julio – Alfonso IX. Madrid: C.S.I.C. - Instituto Jerónimo Zurita, 1944. MARQUES, José – A arquidiocese de Braga no século XV. Lisboa, Imprensa Nacional / Casa da Moeda, 1988. MARQUES, Maria Alegria F. – “A introdução da ordem de Cister em Portugal”. In La introducción del Císter en España y Portugal. Burgos: La Olmeda, 1991, pp. 163-193. MATTOSO, José – A nobreza medieval portuguesa: a família e o poder. Lisboa: Estampa, 1987. OTERO PIÑEYRO MASEDA, Pablo – “Ordenes monásticas: o caso dos bens dos mosteiros galegos em Portugal”. In FONSECA, Luis Adão da (coord.) – Entre Portugal e a Galiza (Sécs. XI a XVII). Um olhar peninsular sobre uma região histórica. Porto: CEPESE / Fronteira do Caos Editores, 2014, pp. 201-204. PALLARES MÉNDEZ, María del Carmen; PORTELA SILVA, Ermelindo – El bajo valle del Miño en los siglos XII y XIII. Economía agraria y estructura social. Santiago de Compostela: Universidad, 1971. PÉREZ RODRÍGUEZ, Francisco Javier – O mosteiro de Melón no século XV. Ourense: Deputación Provincial, 1996. PÉREZ RODRÍGUEZ, Francisco Javier – O mosteiro dos Santos Xusto e Pastor de Toxosoutos na Idade Media (séculos XII-XIII). Sada: Seminario de Estudios Galegos / Ediciós do Castro, 2002. PÉREZ RODRÍGUEZ, Francisco Javier – “Mosteiros e priorados dependentes de San Salvador de Celanova entre 1100 y 1500”. In SINGUL, Francisco (coord.) – Rudesindus. O legado do santo. Santiago de Compostela: Xunta de Galicia, 2007, pp. 204-221. RODRIGUES, Ana Paula Leite – Senhores e camponeses num expaço de fronteira. Estudo da projecção portuguesa do domínio monástico de Santa Maria de Oia nos séculos XII a -XV). Santiago de Compostela: Facultade de Xeografia e Histoira, 2014. Tese de doutoramento. RODRIGUES, Ana Paula Leite – Nos dois lados do rio Minho. O senhorio transfronteiriço do mosteiro de Santa Maria de Oia (Séculos XI a -XV). Vigo: Instituto de Estudios Vigueses, 2017. ROMANÍ MARTÍNEZ, Miguel – El monasterio de Santa Maria de Oseira (Ourense). Estudio histórico (1137-1310). Santiago de Compostela: Universidade, 1989. SILVA, Manuela Santos – Óbidos e a sua região na Baixa Idade Media. Lisboa: Universidade de Lisboa, 1996. Tese de Doutoramento. SOUSA, Bernardo Vasconcelos e (Dir.) – Ordens religiosas em Portugal. Das origens a Trento – Guia Histórico. Lisboa: Livros Horizonte, 2005. SUÁREZ GONZÁLEZ, Ana – “Cistercian Scriptoria in the Twelfth and Thireenth Centuries. A Starting Point”. In D’EMILIO, James (coord.) – Culture and Society in Medieval Galicia. A Cultural Crossroads at the Edge of Europe. Leiden-Boston: Brill, 2015, pp. 765-811.